2020
DOI: 10.3390/app10124114
|View full text |Cite
|
Sign up to set email alerts
|

Frenulectomy with Diode Laser Technology in Paeditric Patients: Quantitative and Qualitative Evaluations. Randomized Double- Blind Clinical Trial

Abstract: Background: Ankyloglossia is an anatomical alteration of the frenulum length, volume, compactness, and insertion. It can lead to alterations in the ability to swallow and chewing, and dysfunctional coordination amongst cranio-facial muscles; these alterations are often responsible for respiratory alterations, skeletal malocclusions and dyslalia or the delay of speech. The aim of this study is to estimate the efficacy of lingual frenulectomy with diode-laser technology through a qualitative and quantitative eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…Sfasciotti et al demonstrated the efficacy of a lingual frenectomy with diode laser technology through a qualitative and quantitative evaluation in pediatric patients [ 28 ]. In this study, one hundred and twenty-five pediatric patients were recruited: 100 with a lingual pathological frenulum randomly divided into four operating groups; the other 25 with a borderline pathological frenulum were recruited as a control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sfasciotti et al demonstrated the efficacy of a lingual frenectomy with diode laser technology through a qualitative and quantitative evaluation in pediatric patients [ 28 ]. In this study, one hundred and twenty-five pediatric patients were recruited: 100 with a lingual pathological frenulum randomly divided into four operating groups; the other 25 with a borderline pathological frenulum were recruited as a control group.…”
Section: Discussionmentioning
confidence: 99%
“…The numerical rating scale (NRS) was adopted for the pain assessment. The NRS pain evaluation system was successfully adopted due to its good reliability and accuracy, as demonstrated in many clinical studies [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The different results described in the studies could derive from the variety of methodologies used to diagnose SRDB and the difficulty in diagnosing a mental problem in children, together with the possibility that behavioral problems are considered as comorbidities and not as diseases directly correlated with OSAS [ 38 , 39 , 40 , 41 ]. This difficulty in evaluation has been highlighted in recent studies, which indicate the need for more clinical trials to better clarify a possible link between SRDB and different comorbidities [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The plaque and bleeding index are above average when there is a high labial frenulum attachment which influences, negatively, the retention of plaque and the insurgence of gingivitis or gingival recession [ 14 ]. The oral surgery approach can be traditional with a scalpel, electrosurgery or with a laser, the use of which is broadening out and succeeding in different branches of dentistry [ 15 , 16 , 17 ]. The advantages of the single kind of lasers are well-showed in literature but, now as then, there are few studies concerning a comparison amongst their surgical performance, especially for the mandibular labial frenectomies [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%